2020
DOI: 10.1111/ene.14353
|View full text |Cite
|
Sign up to set email alerts
|

Active case finding of dementia in ambulatory care settings: a comparison of three strategies

Abstract: Background and purpose To reduce the diagnostic gap of dementia, three strategies can be employed for case finding of cognitive impairment in ambulatory care settings, namely using informant report, brief cognitive test or a combination of informant report and brief cognitive test. The right strategy to adopt across different healthcare settings remains unclear. This diagnostic study compared the performance of the three strategies for detecting dementia (primary aim), as well as for detecting both mild cognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 65 publications
(102 reference statements)
0
3
0
Order By: Relevance
“…Vice versa, among older patients with known SCD, the additional complaints of anxiety symptoms should also not be dismissed as merely a psychological reaction to their concerns about the SCD. On the contrary, anxiety and SCD should be seen as independent predictors of neurocognitive disorders, and the cooccurrence of both should alert clinicians to the much higher risk of neurocognitive disorders, which may then prompt more intensive interventions to prevent cognitive decline (such as those related to risk-factor modification, physical exercise, and cognitive training) [12,13], enrolment into preventive trials for dementia [3,32], and closer monitoring of cognitive function over time to allow timely diagnosis of cognitive impairment [40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…Vice versa, among older patients with known SCD, the additional complaints of anxiety symptoms should also not be dismissed as merely a psychological reaction to their concerns about the SCD. On the contrary, anxiety and SCD should be seen as independent predictors of neurocognitive disorders, and the cooccurrence of both should alert clinicians to the much higher risk of neurocognitive disorders, which may then prompt more intensive interventions to prevent cognitive decline (such as those related to risk-factor modification, physical exercise, and cognitive training) [12,13], enrolment into preventive trials for dementia [3,32], and closer monitoring of cognitive function over time to allow timely diagnosis of cognitive impairment [40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…Such risk stratification can allow clinicians to employ more personalized approaches in patient counseling and management (Liew, 2020c, 2020d), whereby those at imminent risk of neurocognitive disorders may be identified for more intensive interventions (e.g. risk factor modification, physical exercise and cognitive training) (Jessen et al, 2020; Livingston et al, 2020; Ngandu et al, 2015), enrolment into preventive trials (Liew, 2019e, 2020b), as well as closer monitoring of cognitive function over time to allow timely diagnosis of cognitive impairment (Liew, 2019a, 2019c, 2019d, 2020a).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, previous reports showed that passive screening can lead to a false positive and incorrect diagnosis of some psychiatric disorders with dementia (7). Therefore, several scientific bodies have advocated active case-finding in the elderly population using validated cognitive tests and functional questionnaires (8). Despite the potential advantages of active case-finding, there is a lack of population-based studies comparing the effectiveness of active case-finding with passive screening.…”
Section: Introductionmentioning
confidence: 99%